Use of 3D model in the study of tower crane stability - Ivanenko, O. I.; Musaev, Z. R. (Харківський національний автомобільно-дорожній університет, 2015)
The article presents the results of a study of the stability of a tower crane during operation, taking into account the influence of loads on the supports. The results of comparing the distribution of loads on the crane supports determined as a result of mathematical and computer modeling during the turning and lifting of the boom are presented.
Keywords: research; tower crane; stability; load distribution; mathematical model; computer model; adequacy; 621.87